The effects of excess calcium and aging media on mechanical properties of calcium phosphate filling materials - Alqap, Asep Sofwan F.; Sopyan, Iis; -, Suryanto (Trans Tech Publications, Switzerland, 2014)
Abstract. The effect of excess calcium and aging media on calcium phosphate biomaterials mechanical strength was studied. The variation of excess calcium and sample type has shown different performance when they are being aged in the moist environment (ME) and the simulated body fluid (SBF). The calcium phosphates were synthesized via low temperature hydrothermal method and sampled to two types of powder-water (3:2) mixture and paste for 90 days of the aging time. Two mechanical tests were applied, compression and diametrical tensile test, while XRD to evaluate phases. Scanning electron micrograph showed the paste samples that soaked in SBF was better entanglement of the particles, better compression strength but with degradation and diametrical tensile strength improvement by aging. Calcium hydroxide and ammonium di-hydrogen phosphoric was traced in all the samples along with calcium deficient hydroxyapatite as the main phase.